Kajian Parametrik Balok Beton Memadat Mandiri Menggunakan Analisis Nonlinier Elemen Hingga - Effendi, Mahmud Kori; Rahmayanti, Novi; Fathurahman, Ilman (MEDIA KOMUNIKASI TEKNIK SIPIL, 2021)
Self-compacting concrete has self-flowing, viscous and compact properties that minimize mechanical compaction. This concrete is suitable for solving the concrete pouring in the narrow and congested reinforcement. Beams made of both self-compacting concrete and normal high-strength concrete are analyzed by MSC Marc / Mentat software. Steel is modeled by being embedded in concrete. The failure criterion of Linear Mohr-Coulomb is used for concrete and Von Mises for reinforcing steel, respectively. Concrete and the plate support are modelled by 3D solid elements. For the steel, the truss element is used. The contact analysis is implemented between beam and both steel plate and steel supports. The load-deflection curve for both concrete are almost the same as the results of the experimental curve. The results of the contact analysis also showed that there were contact and separation in the contact area. The shear retention factor value close to one meaning will restrain greater loads. The results of the study on the reinforcement ratio also showed a reduction of 70% and an increase of 70% when using minimum and maximum reinforcement, respectively. The larger concrete cover also reduces the load that the beams can restrain.